DEFORMATION FABRICS OF THE CIMA DI GAGNONE PERIDOTITE MASSIF, CENTRAL ALPS, SWITZERLAND: EVIDENCE OF DEFORMATION AT LOW TEMPERATURES IN THE PRESENCE OF WATER - Skemer P.; Katayama I.; Karato S.-I. (My University, 2006)
We report a new observation of the olivine B-type lattice-preferred orientation (LPO), from the garnet peridotite at Cima di Gagnone, Switzerland. The olivine B-type fabric forms at low temperatures and/or high stress in the presence of water, and is of particular interest because it may be used to explain the trench-parallel shear-wave splitting that is often observed at subduction zones. In conjunction with the olivine B-type fabric, we have found strong orthopyroxene LPO that is identical to those formed under water-free conditions. This suggests that water may not have a significant effect on orthopyroxene fabric. From the olivine microstructure, we determine that a stress of 22 ± 8 MPa was applied during the deformation event that formed the olivine LPO. Using an olivine flow-law, and assuming geological strain-rates, we determine the temperature of deformation to be 800 ± 175°C. This does not preclude an ultra-deep origin for the ultramafic rocks at Cima di Gagnone, but indicates that much of the deformation recorded in the microstructure occurred at modest temperatures. © Springer-Verlag 2006.